1 - Teaching and Researching Africa in an ‘Engaged’ Way: The Possibilities and Limitations of ‘Community Engagement’ - Sally Matthews, (Journal of Higher Education in Africa, 2010)
An increasing number of universities around the world are making commit- ments to ‘community engagement’ or some similar term. The idea that uni- versities should engage with their contexts is related to concerns about the relevance of the knowledge being produced by universities today. Such concerns about relevance are familiar to those working in African Studies where there have long been debates about the relevance of the knowledge produced by Africanists. In this article, I draw on some of these debates in African Studies to explore the possibilities and limitations of the idea of community engagement. I argue that it is not possible to produce knowledge that is broadly relevant to ‘the community’ as a whole. Rather, we need to identify for whom exactly we wish to produce relevant knowledge. In order to do this, questions around the politics of knowledge, which have been highlighted in many of the debates about African Studies, must be given further attention.